Mitochondrial 3‐hydroxy‐3‐methylglutaryl‐CoA synthase deficiency: urinary organic acid profiles and expanded spectrum of mutations. Issue 3 (16th December 2014) - Pitt, James J.; Peters, Heidi; Boneh, Avihu; Yaplito‐Lee, Joy; Wieser, Stefanie; Hinderhofer, Katrin; Johnson, David; Zschocke, Johannes
Abstract: Mitochondrial 3‐hydroxy‐3‐methylglutaryl CoA synthase (HMCS2) deficiency results in episodes of hypoglycemia and increases in fatty acid metabolites. Metabolite abnormalities described to date in HMCS2 deficiency are nonspecific and overlap with other inborn errors of metabolism, making the biochemical diagnosis of HMCS2 deficiency difficult. Urinary organic acid profiles from periods of metabolic decompensation were studied in detail in HMCS2‐deficient patients from four families. An additional six unrelated patients were identified from clinical presentation and/or qualitative identification of abnormal organic acids. The diagnosis was confirmed by sequencing and deletion/duplication analysis of the HMGCS2 gene. Seven related novel organic acids were identified in urine profiles. Five of them (3, 5‐dihydroxyhexanoic 1, 5 lactone; trans ‐5‐hydroxyhex‐2‐enoate; 4‐hydroxy‐6‐methyl‐2‐pyrone; 5‐hydroxy‐3‐ketohexanoate; 3, 5‐dihydroxyhexanoate) were identified by comparison with synthesized or commercial authentic compounds. We provisionally identified trans ‐3‐hydroxyhex‐4‐enoate and 3‐hydroxy‐5‐ketohexanoate by their mass spectral characteristics. These metabolites were found in samples taken during periods of decompensation and normalized when patients recovered. When cutoffs of adipic >200 and 4‐hydroxy‐6‐methyl‐2‐pyrone >20 μmol/mmol creatinine were applied, all eight samples taken from five HMCS2‐deficient patients during episodes of decompensation were flagged with a positive predictive value of 80 % (95 % confidence interval 35–100 %). Some ketotic patients had increased 4‐hydroxy‐6‐methyl‐2‐pyrone. Molecular studies identified a total of 12 novel mutations, including a large deletion of HMGCS2 exon 1 in two families, highlighting the need to perform quantitative gene analyses. There are now 26 known HMGCS2 mutations, which are reviewed in the text. 4‐Hydroxy‐6‐methyl‐2‐pyrone and related metabolites are markers for HMCS2 deficiency. Detection of these metabolites will streamline the biochemical diagnosis of this disorder.